Over the hills and far away : last glacial maximum lithic technology around the Great Adriatic Plain - Cancellieri, Emanuele, (Archaeopress archaeology., 2015)
The research scope of this book is the human occupation of the northern Adriatic region at the end of the last glacial maximum and a point of view over the long debated occupation of the once exposed Great Adriatic Plain and the role it played within the early Epigravettian hunter-gatherers settlement system.